Mechanical revascularization using Solitaire AB device for acute limb ischemia secondary to popliteal and infrapopliteal embolic occlusion. (March 2022) - Gong, Maofeng; Zhou, Yangyi; He, Xu; Chen, Liang; Zhao, Boxiang; Kong, Jie; Su, Haobo; Gu, Jianping
Objective: Acute limb ischemia is one of the most common arterial emergencies. The data of mechanical revascularization using Solitaire AB device coupled with thromboaspiration for the treatment of popliteal and infrapopliteal acute limb ischemia are limited. The aim of this study was to review the preliminary safety and effectiveness. Methods: We performed a single-center retrospective review of patients with popliteal and infrapopliteal acute limb ischemia treated with Solitaire AB device coupled with thromboaspiration from February 2019 to May 2020. Adjunctive balloon angioplasty was performed to correct coexisting atherosclerotic stenosis. Technical success was defined as successful deployment of the Solitaire AB device across the occlusive segment and successful retrieval without the use of adjunctive catheter-directed thrombolysis or balloon angioplasty. Clinical success was defined as the relief of symptoms related to acute limb ischemia. Follow-up outcomes were also reviewed. Results: There were 15 consecutive patients who underwent 16 Solitaire AB devices. Technical success was achieved in 11 (73.3%) patients. Of the unsuccessful patients, double-stent retrievers were employed in 1 (6.7%) patient. Two patients who encountered residual clots in distal small arteries underwent adjunctive catheter-directed thrombolysis. An adjunctive balloon angioplasty was required in 1 (6.7%) patient. All patients had notable acute limb ischemia symptom relief after the procedures. Clinical success was achieved in 14 (93.3%) patients. Besides one patient encountered minor amputation, the major amputation was prevented in all patients. No device-related complications or distal embolization events were recorded during the procedures. At the follow-up of 12 months, all surviving patients remained symptom-free, the patency was achieved in 12 (80%) patients and the limb salvage was 100%. Conclusions: Preliminary outcomes suggest that mechanical revascularization using Solitaire AB device coupled with manual thromboaspiration appears to be a rapid, safe, and effective modality that appears to reduce the requirement for catheter-directed thrombolysis. Advances in knowledge: These findings may add a promising recanalization therapy for acute embolic occlusion of the acute limb ischemia secondary to popliteal and infrapopliteal arteries.